ISOLASI DAN KARAKTERISASI Staphylococcus aureus DARI SUSU KAMBING DAN PRODUK OLAHANNYA - Widodo Suwito; Erna Winarti; Ari Widyastuti; Felisitas Kristiyanti; Andriani Andriani (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2017)
Presence of Staphylococcus aureus in goat milk and dairy product could lead to human illness. The aim of the present study was to characterize S. aureus isolated from goat milk and its products. The samples used in these studies were taken from goat farm and a goat milk processing facility in Sleman district. Characterization of the S. aureus was based on biochemical reaction, namely haemolysin activity, clumping factor, coagulase activity, and resistance against antibiotics. The haemolysin activity was determined by culturing the isolates on blood agar plates, whereas clumping factor with slide agglutination test. Mixing the rabbit plasma and culture S. aureus was used to determine the coagulase activity, while antibiotics susceptibility was carried out with agar diffusion test. The resulst showed that the number of S. aureus detected in 86% of goat milk samples conformed with SNI No 01-6366-2000. The characteristics of S. aureus from goat milk samples showed that 80% of the S. aureus isolates were non haemolytic, 20% were positive for clumping factor, and 40% were positive for coagulase activity. The antibiotic resistance test for S. aureus isolated from the goat milk samples suggested that 30% was resistant to ampicillin and penicillin while 10% showed resistance to erythromycin, neomycin, sulfonamide, and tetracycline.